SPATIAL FACTOR OF BANKING OPERATIONS IN KYIV - SIMONOVA, Anna (Ekonomichna ta Sotsialna Geografiya, 2014)
Features of territorial placement of banking institutions in city boundaries of Kyiv are defined, an attempt of establishment of the reasons of unevenness of their dispersal on districts of the capital is made. The priority area of placement of banking institutions is defined

Визначено особливості територіального розміщення банківських установ в межах міста Києва та зроблено спробу встановлення причин нерівномірності їх розташування за районами столиці. Визначено пріоритетний район розміщення банківських установ.
ТЕРИТОРІАЛЬНИЙ ФАКТОР БАНКІВСЬКОЇ ДІЯЛЬНОСТІ МІСТА КИЄВА
Keywords: territorial placement; density; territorial organization; розміщення; концентрація; територіальна організація